The Implementation of Complete Systematic Land Registration (PTSL) Which the Transfer of Rights of His Land Not Using PPAT Deed (Case Study in National Land Agency of Grobogan) - Reni Widayanti; Jeifson Sitorus; Gunarto Gunarto (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2019)
Registration of land as a form of implementation of the government's obligation to guarantee legal certainty and the protection of land ownership. The purpose of this research are: 1) To analyze the Complete implementation of Systematic Land Registration in Grobogan. 2) To analyze barriers that occur in the Implementation of Complete Systematic Land Registration in Grobogan. 3) Analyze solutions to the obstacles to the full implementation of Systematic Land Registration in Grobogan. This study using sociological juridical approach namely a study conducted in depth against the reality-a reality that exist within the community and surrounding environment for the purpose of finding facts there and then will discuss the problems that exist.Based on the results of data analysis concluded that that There are several stages in the implementation of location determination PTSL among other things, education, the establishment of the adjudication committee, the announcement of physical data and juridical. In the implementation of PTSL there are several barriers among others are plots of land still in dispute, plots the subject is still not clear, less pro-active society and other but officials PTSL seeks to overcome these obstacles with solutions that are effective in order stand on PTSL program is going well and smoothly in the interests of the general public.Keywords: Complete Systematic Land Registration; Without PPAT Deed.